DESAIN SARANA PENGISI DAYA PONSEL DI DIREKTORAT POLITEKNIK NEGERI SAMARINDA - Cahyadi, Dwi; Mariska, Lolita (JURNAL KREATIF: DESAIN PRODUK INDUSTRI DAN ARSITEKTUR, 2018)
ABSTRACTEveryday human life is inseparable from the need to communicate. One of the tools commonly used to communicate remotely is mobile. Mobile technology that adopts cutting edge technology is called smartphone. Smartphones are the needs of people who have many benefits, facilitate work, and improve lifestyle. Smartphones can not be used continuously.Smartphones require power to be able to power up and use. A battery charger or battery charger is a device used to recharge energy into the battery by entering an electric current through it. But there are many obstacles that are often experienced when we have to spend the day outside the house, providing limited electricity in public places makes it difficult for us to recharge smartphone bat teries. The need for battery charging continues to increase along with its power consumption. The new innovation of concern is like the means of charging batteries in public places such as the Institute of Education. One of them is the Samarinda State Poly technic. While in public and smartphone batteries are weak, based on convenience aspect, smartphone type and place to charge smartphone battery. Therefore,to design a product that is a convenient means of charging station design and there are various types of chargers that can facilitate visitors to charge the smartphone battery, then made a means Charging Station Directorate of State Polytechnic Samarinda.Keywords: Smartphone, Charger, Institute of Education.